The Structure of Firm-Specific Labour Unions - Thorsten Upmann; Julia Müller (Tinbergen Institute, 2013)
In this paper we investigate trade union formation. To this end we apply a model with two types of labour where both groups decide on whether they prefer to be represented by either two independent craft-specific (professional) labour unions or by a joint (encompassing) labour union. Applying the asymmetric Nash bargaining solution, we find that it is beneficial for at least one group of labourers to resist a unification and to form instead its own independent labour union - and in some cases even both groups are worse off under the umbrella of a joint union. Consequently, a joint union must be considered as a rather unstable institution. As a mirror image, profits are lower if the firm bargains with two independent craft unions. This explains why employers vehemently oppose recent split offs of some occupational groups from existing unions and from stipulated tariff unions.
urn:NBN:nl:ui:15-1765/40417
Keywords: C78; J31; J41; J51; 330; trade-union formation; wage-employment bargains; Nash bargaining solution; encompassing and craft-specific labour unions; trade union merger